Perlindungan Anak dalam Keluarga Poligami Perspektif Kompilasi Hukum Islam - Ayu Rusnita; Sri Susanti Simanjuntak; Yusna Elfrida Br Tambunan; Dian Wahyu Harmoni Sembiring; Sri Hadiningrum (Sharia Journal and Education Center Publishing, 2023)
Abstract The research uses library research sources.The data is obtained from document materials in a normative way, namely interpreting what is countained in law books, as well as existing documents in legislation (Statute Approach). After the data is collected, the data analyzed using qualitative-normative techniques with discussion deductive which discusses child protection in polygamous families in terms of Islamic law. Child protection in polygamous families is viewed from Islamic Law (KHI) and its practive still needs to be improved.Even though the KHI regulates the protection of children in polygamous families, in reality there are still many children who experience violence, discrimination and neglect in polygamous families. For the rights of children who face challenges. In polygamous families, it is hoped that these efforts can produce more optimal child protection designs in polygamous families, so that children can grow develop optimally. Keywords: protection, children, polygamy Abstrak Penelitian ini menggunakan sumber penelitian kepustakaan (library research), data diperoleh dari bahan dokumen dengan cara normatif, yaitu menafsirkan apa yang tertera dalam buku-buku hukum, serta dokumen-dokumen yang ada dalam peraturan perundang-undangan (Statute Approach). Setelah data terkumpul, data dianalisis dengan menggunakan teknik kualitatif-normatif dengan pembahasan secara deduktif yang membahas tentang perlindungan anak dalam keluarga poligami ditinjau dari hukum Islam. Perlindungan anak dalam keluarga poligami ditinjau dari Hukum Islam (KHI) dalam praktiknya masih perlu ditingkatkan, meskipun KHI telah mengatur tentang perlindungan anak dalam keluarga poligami, namun pada kenyataannya masih banyak anak yang mengalami kekerasan, diskriminasi, dan penelantaran dalam keluarga poligami. Untuk hak-hak anak yang menghadapi tantangan. Dalam keluarga poligami, diharapkan upaya-upaya tersebut dapat menghasilkan desain perlindungan anak yang lebih optimal dalam keluarga poligami, sehingga anak dapat tumbuh kembang secara optimal. Kata kunci: perlindungan, anak, poligami